PELAKSANAAN PEMBELAJARAN JARAK JAUH TERHADAP MOTIVASI BELAJAR SISWA/SISWI SMPN 2 KOTO KAMPAR HULU - Riri Junita; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Implementation of long-range learning to mode learning SMPN 2 Koto Kampar Hulu student’s. This study was conducted specifically on the school superintendent VII class up to date IX class to the Bandur Picak village, Kecamatan Koto Kampar Hulu, Kabupaten Kampar. The purpose of this study is to know how to perform the long-range learning at the junior high and know how to motivate learn student. The methods in this research are using a quantitative approach with quantitative is a descriptive that is the conclusion to the research done and got an analysis of the sample and subjects it can be imposed for the population. Subjective testing of this research uses a census of which the whole student will be 89 student’s. The theory used in this study is the motivation theory that McDonald came up with the results of the further study know that the performance of long range learning consists of four indicators that both tools and infrastructure fall at a moderate percentage of 100%. Ability tu use tecnhology is moderate or with a percentage of 70,1%. A moderate category of internet connection or a percentage of 77,1%. The teacher’s creativity in teaching is high in category or with a 79,8%. While the motivation for learning is two indicators: intrinsic factors are moderate or with a percentage of 87,6% and extrinsic factors at a high rating of 48,3%. Extrinsic factors are categorically high because at present levels 50,1% are effected as low as 1,6%. The percentage difference between low levels and high levels is too far away, so extrinsix factors fall into a high category of student learning motivation.   Keywords: remote learning, motivation learning, motivation theory.